Study on the mechanism of action of Qiju Dihuang Pills in the treatment of dry eye based on network pharmacology and molecular docking - Xu Chen; Liang Pengfei; Shi Ruodi; Yu Yang (Guoji laonian yixue zazhi)
[Objective] To explore the active ingredients and mechanism of action of Qiju Dihuang Pills in the treatment of dry eye by network pharmacology and molecular docking. [Methods] The active ingredients of Qiju Dihuang Pills were obtained from TCMSP and Pharmacopoeia of the People’s Republic of China, and their targets were converted into standard gene names through the UniProt platform. Disease targets were screened from GeneCards, OMIM and DisGeNET databases. The Cytoscape 3.9.1 software was used to construct and analyze the compound network to obtain the main active ingredients of the drug. Protein interactions between genes intersecting with Qiju Dihuang Pills and dry eye were analyzed on the STING platform, and then imported into the software to screen for key targets. The intersection genes were analyzed for GO function and KEGG pathway enrichment using the DAVID database, and finally, molecular docking validation was completed by AutoDock 4.2.6 software. [ Results] 149 active ingredients of Qiju Dihuang Pills and 2 014 dry eye targets were screened, with a total of 89 intersection genes between them. The main active ingredients were quercetin, kaempferol, luteolin, beta-sitosterol, naringenin, stigmasterol, isorhamnetin, and the key targets included Protein kinase B(AKT)1,tumor necrosis Factor(TNF), tumor protein P53 (TP53), interleukin 6 (IL6), interleukin1 beta (IL1B), estrogen receptor 1 (ESR1). Key pathways included the advanced glycation end-products(AGE)-receptor for advanced glycation end-products(RAGE) signaling pathway in diabetic complications, phosphoinositide 3-kinase(PI3K)-AKT signaling pathway, mitogen-activated protein kinase(MAPK) signaling pathway, etc. [Conclusion] Qiju Dihuang Pills may treat dry eye through the action of quercetin on key targets such as AKT1, TNF, TP53, IL6 and so on. It can exert anti-inflammatory and inhibit apoptosis by regulating the AGE-RAGE signaling pathway, PI3K-AKT signaling pathway and MAPK signaling pathway.